Morphology of Khorgo Volcano Crater in the Khangai Mountains in Central Mongolia - Enkhbold, Altanbold; Khukhuudei, Ulambadrakh; Dorjgochoo, Sanchir; Ganbold, Byambabayar (Proceedings of the Mongolian Academy of Sciences, 2020)
Cenozoic basalt, which is widespread in Mongolia, has been attracting the attention of Central Asian researchers since the beginning of the last century. This study identified the geomorphological shape of the Khorgo volcano. The main purpose of the study is to determine the origin and morphological form of Khorgo volcano, a key representative of Cenozoic volcanism. In general, there are several types of morphological forms associated with lava overflow, and it is important to determine which types are the most common and also to establish a link between them. Geomorphological studies in this area have not been conducted in Mongolia. Spatial improvement and morphometric methods satellite imagery had identified Khorgo volcanic faults. Khangai magmatism had thinned its crust to 45 km during the Tariat-Chuluut volcanic activity. It can be concluded that this was due to the thinning of the continental crust in the Khangai Mountains because of mantle plume. During this time, tectonic faults formed were formed, which had broken through the earth's crust. Part of this fault was formed in the vicinity of Khorgo Mountain from northwest to southeast, and lava flowed with the basic composition, which led to the formation of the current morphological form of Khorgo volcano. The lava flow was less than 45% silica and potassium-dominated, which blocked the Suman River valley and formed the present-day Terkhiin Tsagaan Lake. The morphometric analysis compared the morphology of a typical volcano, which showed that the mouth of the crater of the Khorgo volcano has a slope slanting about 45 degrees, it is about 100 meters in depth, with a diameter of about 500 meters. By comparing the basalt composition of the Khorgo volcano and its morphometric characteristics with other standard volcanoes, it has been determined that it is in the form of a lava dome.